Nazwy własne w powieści W zaraniu Teodora Tomasza Jeża - Żuraszek-Ryś, Iwona (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
The article presents the proper names from the novel W zaraniu by T. T. J eż. The subject of the overview focuses on oikonyms and anthroponyms, with particular emphasis on the relation of literary naming to authentic onyms. Additionally, the functional aspects of the selected types of names are examined. Simultaneously, the article analyses the specific solutions adopted by T. T. J eż, conditioned by the character of his literary production.